Change in alcohol and tobacco consumption after a diagnosis of head and neck cancer: Findings from Head and Neck 5000. Issue 7 (27th February 2018) - Penfold, Chris M.; Thomas, Steven J.; Waylen, Andrea; Ness, Andrew R.
Abstract: Background: Tobacco and alcohol consumption are risk factors for developing head and neck cancer, and continuation postdiagnosis can adversely affect prognosis. We explored changes to these behaviors after a head and neck cancer diagnosis. Methods: Demographic and clinical data were collected from 973 people newly diagnosed with oral cavity, oropharyngeal, or laryngeal cancer. Tobacco and alcohol consumption were additionally collected 4 and 12 months later. Results: The prevalence of high alcohol consumption reduced from 54.3% at diagnosis to 41.4% at 12 months, and smoking reduced from 21.0% to 11.7%. Changes in behavior were dynamic, for example, 44% of smokers at 12 months were not smoking at diagnosis or 4 months. Several factors were associated with alcohol consumption, whereas only tumor site and comorbidities were associated with smoking. Conclusion: A diagnosis of head and neck cancer can result in important changes in alcohol consumption and smoking prevalence. However, these changes are dynamic in the first year after diagnosis.